Use of crack in pregnancy: repercussions for the newborn - Modernel Xavier, Daiani; Calcagno Gomes, Giovana; Portella Ribeiro, Juliane; Soares Mota, Marina; Quadros Alvarez, Simone (Investigación y Educación en Enfermería, 2017)
Objective. To know the effects for the newborn of the use of crack in pregnancy. Methods.This is a qualitative study conducted in a university hospital in southern Brazil, in the first half of 2014. Fifteen mothers crack users and five grandparents participated. The data were produced through semi-structured interviews and later submitted to content analysis. Results. It was found that the use of crack in pregnancy leads to repercussions related to the health of the newborn and repercussions related to family restructuring. In relation to the newborn, prematurity, congenital malformation, hospitalization in an intensive care unit, use of care and feeding technologies through artificial milk formulas were mentioned. In the family context, it was evidenced the occurrence of abandonment of the child by the mother, causing the adoption of the newborn by relatives of the family nucleus or their institutionalization due to lack of family structure. Conclusion. It was found that the use of crack in pregnancy leads to repercussions related to the health of the newborn and repercussions related to family restructuring. In this sense, the recruitment of pregnant users of crack by health/nursing professionals and referral for high-risk prenatal care, as well as early identification of the peculiarities of the newborns of these women, and the development of actions that minimize the repercussions of crack are imperative. How to cite this article: Xavier DM, Gomes GC, Ribeiro JP, Mota MS, Alvarez SQ. Use of crack in pregnancy: repercussions for the newborn. Invest. Educ. Enferm. 2017; 35(3): 260-267